Air mobility of people and airport growth potential in regions of Russia - Ryazanov, Vlas (Bulletin of Geography. Socio-economic Series, 2013)
The article is about Russian regional airports, air mobility of people in regions of Russia, geographical distribution and results of econometric forecasting of these figures based on demographic and economic factors. Also some historical reviews, a description of the current situation and international comparisons are provided. The research revealed that people’s income and investment (both current and accumulated) are the main factors affecting air transportation growth in the studied airports. In the long-term perspective air traffic of Russian airports can triple by 2030, while Russian air mobility figures can exceed the present ones in Western Europe.